Fabrication of biodegradable poly(lactic acid) particles in flow-focusing glass capillary devices - Goran Vladisavljevic; J.V. Henry; Wynter J. Duncanson; Ho Cheung Shum; David A. Weitz (2012)
Monodisperse poly(dl-lactic acid) (PLA) particles with a diameter in the range from 12 to 100 9m were fabricated in flow focusing glass capillary devices by evaporation of dichloromethane (DCM) from emulsions at room temperature. The dispersed phase was 5% (w/w) PLA in DCM containing a small amount of Nile red and the continuous phase was 5% (w/w) poly(vinyl alcohol) in reverse osmosis water. Particle diameter was 2.7 times smaller than the size of the emulsion droplet template indicating that the particle porosity was very low. SEM images revealed that the majority of particle pores are in the sub-micron region but in some instances these pores can reach 3 9m in diameter. Droplet diameter was influenced by the flow rates of the two phases and the entry diameter of the collection capillary tube; droplet diameters decreased with increasing values of the flow rate ratio of the dispersed to continuous phase to reach constant minimum values at 40-60 % orifice diameter. At flow rate ratios less than 5, jetting can occur, giving rise to large droplets formed by detachment from relatively long jets (~10 times longer than droplet diameter).